Elaborasi Ontologis-Normatif Ketuhanan Non-Dualis dalam Advaita Vedānta sebagai Landasan Etika Bumi bagi Ekoteologi Kontemporer - Puspo Renan Joyo; Krisna S. Yogiswari; I Wayan Salendra; Ni Luh Ersania (Jurnal Penelitian Agama Hindu, 2026)
This study is grounded in the view that the ecological crisis constitutes a systemic polycrisis rooted not only in technological or policy failures but also in ontological assumptions that separate humans from nature. Although Advaita Vedānta is frequently associated with environmental ethics, existing scholarship largely remains at the level of metaphysical alignment without developing an operational normative framework. Accordingly, this research aims to explore Advaita Vedānta ontology as a foundation for ecological ethics through dialogue with contemporary ecotheology. It adopts a qualitative-philosophical method based on Gadamerian hermeneutics (fusion of horizons), interpreting the Upanishads and the Bhagavad Gita contextually while reconstructing the concepts of Brahman, Ātman, māyā, and avidyā to uncover their ethical implications. The findings demonstrate that the non-dual ontology of Advaita Vedānta can be transformed into a normative basis for ecological ethics through principles of ontological identity and self-extension, affirming the unity of all reality in Brahman. Moral awareness thus emerges as an expression of self-realization rather than an externally imposed duty. This framework bridges the gap between metaphysics and praxis by articulating ethical principles such as ahiṃsā, karuṇā, and sevā as concrete expressions of non-dual consciousness in ecological action. The study contributes to the development of an Advaita-based ecological ethics by integrating metaphysical insights with ethical praxis, reinterpreting ecological responsibility as a relational and transformative orientation rooted in non-dual unity. Ultimately, Advaita Vedānta offers a coherent ecotheological framework in which ecological responsibility arises as a rational and existential consequence of realizing the unity of reality.